TAMAN EDUKASI AKTING DI BANJARBARU - Utomo, Dopi Restu; Mentayani, Ira (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The Acting Education Park is a place to practice acting and a public open space for the process of acting practice activities. The design of the Acting Educational Park was motivated by the lack of acting training places in Banjarbaru and the increasing growth of the economy and the creative industry, especially the film sector and the like. The design problem is a park that can accommodate acting training activities and the community can also participate in public spaces. The method used is using architectural programming. The solution uses elements of basic training in acting, namely body exercise, vocal exercise, and mental exercise, and is developed into the design of the Acting Education Park.